MULTI-OBJECTIVE OPTIMAL DESIGN OF ALUMINUM CELL - YANG EChuan; HUANG Lu; PANG Tong; ZHANG ZhenHua; YUAN TianXun (Jixie qiangdu)
On the basis of verifying the effectiveness of the simulation method,frontal collision models of the trolley with three different forms of multi-lattice crash box were established. Through 100% forward collision simulation,the energy absorption effect,crushing performance and peak crushing force of different types of crash box were analyzed. The orthogonal experiment was completed with full factor experimental design method,and the nine-lattice energy absorption box was determined as a follow-up research object,explore the effect of wall thickness on the crashworthiness of crash box,A neural network model was used to construct the proxy model,and the multi-objective optimization design was completed using the NSGA-II genetic algorithm. For the optimized nine-lattice energy absorption box,The energy absorption was increased,the peak crushing force was reduced and the lightweight is achieved.